Identifying the Drivers of Spatial Taxonomic and Functional Beta-Diversity of British Breeding Birds - Wayman, Joseph P.; Sadler, Jonathan P.; Pugh, Thomas A. M.; Martin, Thomas E.; Tobias, Joseph A.; Matthews, Thomas J. (Frontiers in Ecology and Evolution, 2021)
Spatial variation in community composition may be driven by a variety of processes, including environmental filtering and dispersal limitation. While work has been conducted on the relative importance of these processes on various taxa and at varying resolutions, tests using high-resolution empirical data across large spatial extents are sparse. Here, we use a dataset on the presence/absence of breeding bird species collected at the 10 km x 10 km scale across the whole of Britain. Pairwise spatial taxonomic and functional beta diversity, and the constituent components of each (turnover and nestedness / richness loss or gain), were calculated alongside two other measures of functional change (mean nearest taxon distance and mean pairwise distance). Predictor variables included climate and land use measures, as well as a measure of elevation, human influence, and habitat diversity. Generalised dissimilarity modelling was used to analyse the contribution of each predictor variable to variation in the different beta diversity metrics. Overall, we found that geographical distance was the strongest predictor of both taxonomic and functional beta-diversity, and their turnover components, highlighting the role of dispersal limitation in community dissimilarity. Climate, land use, and human influence all contributed to the observed patterns, but to a lesser degree. However, both taxonomic nestedness and functional nestedness were better predicted by a combination of land use, human influence, elevation, and climate variables, indicating a key role for environmental filtering. These findings may have important conservation implications in the face of a warming climate and future land use change.